Pendekatan Normativitas dan Historisitas serta Implikasinya dalam Perkembangan Pemikiran Islam - Nasitotul Janah (Cakrawala: Jurnal Studi Islam, 2018)
Islam is a religion that demands autonomy and must not be distorted. But in its function as a worldview, it is always faced with the progressivity of human life’s problem that is able to accommodate the changes. In this context, there are two approaches in Islamic studies; normative and historical approaches, both have different implications. The normative approach focuses on respecting normative values and the sacredness of the text. The Implication is understanding of Islam becomes very legal-formal and rigid. Islamic scholarship becomes repetitive and involutive, which is often paradox with humanitarian problems. While the historical approach is more focused on the substantial meaning behind religious symbols and texts. The implication is Islamic studies are becoming more progressive and compatible with the progress of life. However, this approach often criticized will make Islam lose its intensity